Predicting Marital Adjustment Based on Resilience and Social Self-Efficacy in Married Men in District 3 of Tehran - Vanaki, Hamid; Azad Yekta, Mehrnaz (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to predict marital adjustment based on resilience and social self-efficacy among married men residing in District 3 of Tehran.Methods and Materials: The research employed a descriptive-correlational design. The statistical population included all married men in District 3 of Tehran who were accessible at the time of the study. Using the formula N ≥ 50 + 8M, a sample of 130 participants was selected through convenience sampling. Data were collected using the Dyadic Adjustment Scale (Spanier, 1976), the Connor-Davidson Resilience Scale (CD-RISC, 2003), and the Social Self-Efficacy Scale (Smith & Betz, 2000). Descriptive statistics and inferential analyses, including Pearson correlation and multiple linear regression, were conducted using SPSS-20 software to evaluate the predictive relationship between the independent variables (resilience and social self-efficacy) and the dependent variable (marital adjustment).Findings: The results of the multiple regression analysis showed that resilience and social self-efficacy significantly predicted marital adjustment. The model accounted for 12.3% of the variance in marital adjustment (R² = 0.123; adjusted R² = 0.119), and the regression model was statistically significant (F(2,127) = 2.74, p = 0.033). Both resilience (β = 0.146, p = 0.008) and social self-efficacy (β = 0.129, p = 0.005) had positive and significant standardized beta coefficients, indicating that higher levels of resilience and social self-efficacy were associated with better marital adjustment in the participants.Conclusion: The findings highlight the importance of psychological resources, specifically resilience and social self-efficacy, in predicting marital adjustment in married men. These results support the development of counseling interventions and educational programs that aim to strengthen these traits to enhance marital quality and relational satisfaction.